STAT1-mediated inhibition of FOXM1 enhances gemcitabine sensitivity in pancreatic cancer. (1st March 2019) - Liu, Chao; Shi, Jiaqi; Li, Qingwei; Li, Zhiwei; Lou, Changjie; Zhao, Qi; Zhu, Yuanyuan; Zhan, Fei; Lian, Jie; Wang, Bojun; Guan, Xin; Fang, Lin; et al.
Abstract : Forkhead box protein M1 (FOXM1) was identified as an oncogenic transcription factor and master regulator of tumor progression and metastasis. FOXM1 expression often correlates with poor prognosis and chemotherapy resistance. In the present study, we investigated the association of FOXM1 expression and chemoresistance in pancreatic cancer. Elevated FOXM1 protein levels were associated with gemcitabine chemoresistance in patients with pancreatic cancer. In gemcitabine resistance cell line models of pancreatic cancer, FOXM1 expression increased, which induced gemcitabine chemoresistance in vitro . In pancreatic cancer cells treated with gemcitabine, FOXM1 affected nuclear factor κB (NF-κB) signaling activity. Immunohistochemical analysis demonstrated a negative association of FOXM1 expression and the level of phosphorylated signal transducer and activator of transcription 1 (pSTAT1) in human pancreatic cancer tissues. Dual-luciferase reporter assays and chromatin-immunoprecipitation assays demonstrated that pSTAT1 directly binds to the FOXM1 promoter to down-regulate its transcription. Interferon γ (IFNγ) promoted gemcitabine-induced cell apoptosis and inhibited cell proliferation in vitro and in vivo by FOXM1 inhibition. These data suggested that FOXM1 enhances chemoresistance to gemcitabine in pancreatic cancer. IFNγ could be used to down-regulate the expression of FOXM1 through STAT1 phosphorylation, thereby increasing the sensitivity of pancreatic cancer cells to gemcitabine. These studies suggested the sensitization by IFNγ in pancreatic ductal adenocarcinoma (PDAC) chemotherapy, which requires further clinical studies.